SÍNTESE DE NANOFIOS DE MnCo E APLICAÇÃO EM SUPERCAPACITORES. - FIGUEIREDO, Patrick Benedito Silva De (2021)
The use of supercapacitors has been widely studied as a highly advantageous device for storing energy, and this principle of energy storage is based on electrochemical reactions, and this device could be a future replacement for batteries as we know them today. For greater efficiency, nanostructured catalysts, such as nanosheets, nanoflakes and nanowires, gained prominence due to a greater surface area and availability of short electron and ion transport pathways, ensuring an increase in the performance of these devices. This work promoted the synthesis of a mixed oxide of MnCo in the form of nanowires prepared with a hydrothermal approach in which the precursors containing the metals of interest were mixed with an oxidizer in heated deionized water. Through the MEV and XPS analysis it was possible to prove the state of nanowires for the material as well as its elements containing the metals oxygen and carbon. Voltammetric experiments showed oxidation peaks related to Cobalt and Manganese oxides. The charge and discharge test demonstrates an extremely high specific capacitance reaching 3204 F∙g-1 at 1 A g-1 . The almost absence of a semicircle in the high frequency region, shown in the electrochemical impedance measurements, may indicate a material with little resistance to energy transfer, which gives the nanowires a high conductivity. By mounting a hybrid supercapacitor with active carbon as the negative side, a very efficient device is obtained, obtaining energy density and power density values at 1 A g-1 . of 48.08 Wh∙kg-1 and 2336.4 W∙kg-1 respectively.